Beyond the cutting edge? : Yoder, technology, and the practices of the church - Heidebrecht, Paul C. (Eugene, Oregon : Pickwick Publications, 2014)
A quick scan of any newsstand is enough to confirm the widespread preoccupation with technological change. As a myriad of articles and advertisements demonstrate, not only are we preoccupied with technology, but we are bombarded with numerous reminders that the cutting edge is in constant motion. Most often the underlying assumption of Christians is that we have no choice but to find ways to cope with the latest and greatest. Indeed, it is often assumed that the church has no choice but to find ways to cope with its new technological context. This book does not make the same assumptions. Building on the work of Mennonite theologian John Howard Yoder, it argues that the practices of the church make it possible for Christians to conscientiously engage technology. This happens when we recognize that marks of the church such as patience, vulnerability, and servanthood can put technological ideals such as speed, control, and efficiency in their proper place. In the course of grappling with three examples of morally formative technologies--automobiles, genetically modified food, and the Internet--this book goes beyond Yoder's thought by emphasizing that the church also plays a crucial role in our moral formation. -- Back cover.
The theological significance of technology -- Using the work of John Howard Yoder as a resource for engaging technology -- The moral vision embodied and encouraged by three particular technologies -- Conscientiously engaging technology through the practices of the church -- Not engineering, but doxology? -- Continuing to test Yoder with technology.
Includes bibliographical reference (pages 205-228) and index.
Print version record.
Keywords: Technology -- Religious aspects -- Christianity; Church -- Marks; Yoder, John Howard; Yoder, John Howard; Church -- Marks; Technology -- Religious aspects -- Christianity; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books